Recent Research Progress of Wound Healing Biomaterials Containing Platelet-Rich Plasma - Huang S; Li Q; Li X; Ye H; Zhang L; Zhu X (International Journal of Nanomedicine)
Sha Huang,1 Qing Li,2 Xiangyu Li,1 Hailing Ye,1 Luyang Zhang,1 Xiaoyi Zhu3,4 1Department of Plastic Surgery, Shulan (Hangzhou) Hospital, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Electrocardiogram, The Second Affiliated Hospital, Zhejiang University School of College, Hangzhou, Zhejiang, People’s Republic of China; 3Department of General Surgery, Shulan (Hangzhou) Hospital, Hangzhou, Zhejiang, People’s Republic of China; 4Department of General Surgery, The Affiliated Hospital of Hangzhou Normal University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xiaoyi Zhu, Email buruouyu@163.comAbstract: Platelet-Rich Plasma (PRP) is a plasma product obtained by centrifuging autologous blood, containing a high concentration of platelets, white blood cells, and fibrin. PRP is enriched with various growth factors, such as Transforming Growth Factor-beta (TGF-β), Platelet-Derived Growth Factor (PDGF), Epidermal Growth Factor (EGF), Insulin-Like Growth Factor (IGF), and Vascular Endothelial Growth Factor (VEGF), all of which promote tissue growth and repair. Currently, PRP has been widely applied in the clinical field of wound repair and has achieved certain therapeutic effects. Biomaterials, as an important direction in the treatment of wounds, combined with PRP, provide new possibilities to enhance the regenerative repair of wounds by PRP. This article reviews the latest research progress of biomaterials combined with PRP in the treatment of wounds, aiming to provide references for PRP wound treatment, as well as to provide ideas for the development of subsequent medical materials. Keywords: platelet-rich plasma, prp, wound healing, biomaterials, hydrogel, wound dressing